2014
DOI: 10.1007/s11239-014-1071-8
|View full text |Cite
|
Sign up to set email alerts
|

In vivo thrombolysis with targeted microbubbles loading tissue plasminogen activator in a rabbit femoral artery thrombus model

Abstract: The increasingly high incidence of ischemic stroke caused by thrombosis of the arterial vessels is one of the major factors that threaten people's health and lives in the world. The present treatments for thrombosis are unsatisfactory yet. We developed the microbubbles loading tissue plasminogen activator (tPA) and their in vitro thrombolysis efficacy under ultrasound exposure has been proved previously. We tried to investigate their thrombolysis effect in vivo in this present study. Thrombus model was made by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…There are many combination of ultrasound activated MB with intravenous tPA for ischemic stroke treatment, while tPA-loaded MB are relatively less reported. MB loaded with tPA and modified with Arg-Gly-Asp-Ser tetrapeptide (RGDS) was prepared by lyopyilization, in vitro studies and an in vivo rabbit femoral artery thrombus model proved that the resulted targeted tPA-loaded MB showed reduced tPA dosage, satisfactory thrombolytic efficacy, and potentially decreased hemorrhagic risk under ultrasound exposure 65, 66 . Lately, coaxial electrohydrodynamic atomization technique was employed to fabricate tPA-loaded MB for potential theranostic application, using sulphur hexafluoride (SF6) as the core and lipid as the shell material generated MB with an average minimum size of ~8 μm and less bubble aggregation 67 , maximum tPA payload can reach 109.89 μg tPA/ml MB and tPA maintained at lease ~80% of its activity 68 .…”
Section: Nanocarriers For Tpamentioning
confidence: 99%
“…There are many combination of ultrasound activated MB with intravenous tPA for ischemic stroke treatment, while tPA-loaded MB are relatively less reported. MB loaded with tPA and modified with Arg-Gly-Asp-Ser tetrapeptide (RGDS) was prepared by lyopyilization, in vitro studies and an in vivo rabbit femoral artery thrombus model proved that the resulted targeted tPA-loaded MB showed reduced tPA dosage, satisfactory thrombolytic efficacy, and potentially decreased hemorrhagic risk under ultrasound exposure 65, 66 . Lately, coaxial electrohydrodynamic atomization technique was employed to fabricate tPA-loaded MB for potential theranostic application, using sulphur hexafluoride (SF6) as the core and lipid as the shell material generated MB with an average minimum size of ~8 μm and less bubble aggregation 67 , maximum tPA payload can reach 109.89 μg tPA/ml MB and tPA maintained at lease ~80% of its activity 68 .…”
Section: Nanocarriers For Tpamentioning
confidence: 99%
“…In-vitro studies have demonstrated enhanced thrombolytic efficacy of t-ELIP and ultrasound over rt-PA alone (Shaw et al 2009), or over rt-PA, ultrasound and Optison™ combined (Tiukinhoy-Laing et al 2007). Hua et al (2014) treated thrombi in a rabbit femoral artery using targeted microbubbles loaded with rt-PA and 2-MHz ultrasound. The recanalization rates obtained with rt-PA targeted microbubbles were similar to those with a combination of untargeted microbubbles and free rt-PA.…”
Section: 3 Experimental Evidence For Ultrasound-enhanced Efficacymentioning
confidence: 99%
“…In particular, the hydrodynamic conditions in occluded vessels represent a major challenge because they severely limit the number of microbubbles that can be delivered to and retained at the site of a thrombus (de Saint Victor et al 2017). Conjugation of antibodies to the microbubble surface has been investigated as a means of increasing the proximity between microbubbles and the thrombus surface, thereby enhancing their lytic effect (Hagisawa et al 2013;Hua et al 2014). This approach, however, does not address the challenge of delivering a sufficient concentration of microbubbles to the clot initially.…”
Section: Introductionmentioning
confidence: 99%